Induction program structures as mediating factors for coach influence on novice teacher development. Issue 5 (19th October 2020) - Mitchell, Douglas E.; Kwok, Andrew; Huston, Debbee
ABSTRACT: This mixed methods study explores a comprehensive survey administered in one induction program of over 2000 novice teachers and 1000 of their coaches. Quantitative analyses through Structural Equation Modeling indicate the mediating impact that coaches have on various design features of induction, which then have an impact on novice teacher learning and pedagogy. Qualitative analyses of comments reveal respondent satisfaction with programmatic structures in influencing their induction experiences while reiterating the importance of coaching. Findings have two main implications: 1) the impact of quality coaching for novice teacher professional growth, in conjunction with the importance of matching novice teachers and their coaches appropriately, and 2) the significance of curriculum, technology, and customer service in having an impact on the overall novice teacher and coach experience throughout induction. These findings have implications for the work of coaching and design features of induction programs.